2021
DOI: 10.1080/13691457.2021.1918064
|View full text |Cite
|
Sign up to set email alerts
|

‘Easy ride or born to be wild'? The travelling of evidence-based social work to Sweden

Abstract: The starting point of this article is an interest in understanding what happens when the concept of evidence-based practice (EBP) travel between countries. Understanding knowledge as something constructed between actors who shape and trade ideas and experiences, the aim is to study how EBP has been received, interpreted and practised in Swedish social work in comparison to some of the other Nordic welfare states. This is done through a scoping study literature review of research on evidence-based practice (EBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Likt de resultat som påvisats från ett flertal nationella kontexter har även svensk forskning visat att socialarbetare i låg utsträckning använt sig av forskning i sitt arbete (Bergmark & Lundström, 2011;Liedgren & Kullberg, 2022). Nordgren och medförfattare (2022) fann att socialarbetare som arbetade som LSS-handläggare använde olika kunskapskällor i sin yrkesutövning.…”
Section: Tidigare Forskningunclassified
“…Likt de resultat som påvisats från ett flertal nationella kontexter har även svensk forskning visat att socialarbetare i låg utsträckning använt sig av forskning i sitt arbete (Bergmark & Lundström, 2011;Liedgren & Kullberg, 2022). Nordgren och medförfattare (2022) fann att socialarbetare som arbetade som LSS-handläggare använde olika kunskapskällor i sin yrkesutövning.…”
Section: Tidigare Forskningunclassified
“…Moreover, the experts of social work were appointed in every institution due to the need for the welfare of human beings (Jia & Li, 2021;Kurnia et al, 2021;Malfitano et al, 2021). It is revealed that social welfare officers were recruited in health and other institutions to take proper care of the people and particularly the affected (Lei et al, 2021;Liedgren & Kullberg, 2021;O'Sullivan & Cooper, 2021). As the implications of social work were adopted by the developed nations in every sphere of life (Lei et al, 2021;Liedgren & Kullberg, 2021;O'Sullivan & Cooper, 2021;Sanfelici, 2021;Shanks & Mejdell Bjerland, 2021;Sicora et al, 2021;Smolle & Espvall, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is revealed that social welfare officers were recruited in health and other institutions to take proper care of the people and particularly the affected (Lei et al, 2021;Liedgren & Kullberg, 2021;O'Sullivan & Cooper, 2021). As the implications of social work were adopted by the developed nations in every sphere of life (Lei et al, 2021;Liedgren & Kullberg, 2021;O'Sullivan & Cooper, 2021;Sanfelici, 2021;Shanks & Mejdell Bjerland, 2021;Sicora et al, 2021;Smolle & Espvall, 2021). It was primarily declared as a full-fledged discipline then it was transformed into every sphere to ensure the welfare of the people.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation